SEGMENTASI OBJEK BERBASIS GAMBAR THERMAL MENGGUNAKAN DEEP LEARNING (PRE-TRAINED RESNET 152) - Noviely, Isra Fanliv; Satyawan, Arief Suryadi; Puspita, Heni (Akademi Angkatan Udara, 2022)
The latest technological developments in the field of Artificial Intelligence have very rapid capabilities and are able to produce systems that facilitate human activities, especially in the field of transportation, especially driving cars or autonomous electric cars. Artificial Intelligence technology itself is able to support success for object detection by detecting objects using semantic segmentation. Neural Network and Image processing are methods used to detect objects semantically as input signal processing in the form of images, and the FLIR thermal camera is used as input from the vehicle. The deep learning method uses a Fully Convolutional Network (FCN) with a Residual Network (ResNet) architectural model as its feature extraction. ResNet is an architectural model from FCN that works from this architectural model not to decline even though the architecture is getting deeper, so it can help humans to drive more productively. The method used in this final project is automatic extraction using deep learning technology with Residual Neural Network 152 (ResNet) architecture. The performance of the semantic segmentation system was tested with 3040 image frames offline using 800 labeled data sets. This method has an extraction accuracy for autonomous vehicle function training reaching 96% with a resolution of 640x512 pixels. The performance of the segmentation system resulted in 18576 image frames in good category, 9333 image frames in sufficient category and 6121 image frames in poor category.